(3GdUfGYJjfs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ehdi fYeI s
(3BNQgG (B:s
(3CKfGA GdaUd GdKGdK ef GdHGH GdYGTQ ai GdNQhL ef GdJTHjH Edi GdeOM s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1082s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdHdGZIs